Administrative Appeal Decision on Dismissal of Civil Servants After Serving Criminal Sentences - Yuli Mega Anggraeni; Taufiqurrohman Syahuri; Irwan Triadi (Journal of Law Perspectives Review, 2026)
This study examines the legal certainty of administrative appeals against the dismissal of civil servants (PNS) after serving criminal sentences, focusing on the role and authority of the State Civil Apparatus Advisory Board (BPASN). Using a normative juridical method with statutory and conceptual approaches, this research analyzes relevant legislation, legal doctrines, and a concrete case involving the dismissal of a civil servant despite evidence of timely reinstatement efforts. The findings reveal that the application of administrative law in such cases tends to be overly formalistic, often disregarding substantive evidence that reflects compliance with legal obligations. This condition undermines the principle of legal certainty, which requires not only clarity of norms but also consistency and fairness in their application. Furthermore, the study highlights the significant role of BPASN as a quasi-judicial body that ensures legal protection through material examination of facts and correction of administrative errors. From the perspective of proportionality, the imposition of dismissal as a severe sanction is deemed inappropriate when mitigating factors and good faith actions are evident. Therefore, the study concludes that achieving legal certainty in civil servant dismissal cases requires a balanced approach that integrates formal procedures, substantive justice, and careful administrative judgment.